Relationship satisfaction in the early stages of the COVID-19 pandemic: A cross-national examination of situational, dispositional, and relationship factors - Vigl, Julia; Strauss, Hannah; Talamini, Francesca; Zentner, Marcel (PLOS ONE, 2022)
The outbreak of the COVID-19 pandemic has had a large impact on various aspects of life, but questions about its effects on close relationships remain largely unanswered. In the present study, we examined perceived changes in relationship satisfaction at the beginning of the COVID-19 pandemic by using an international sample of 3,243 individuals from 67 different countries, mostly from Italy, the United States, the United Kingdom, Germany, Austria, and Switzerland. In April and May 2020, participants responded to an online survey that included questions about relationship satisfaction, their satisfaction before the pandemic, other relationship aspects (e.g., shared time), special circumstances (e.g., mobility restrictions), and enduring dispositions (e.g., insecure attachment). A decline in time shared with one’s partner was most strongly associated with perceived decreases in relationship satisfaction, resulting in a different pattern of findings for cohabiting and non-cohabiting individuals. Among the most influential moderators were anxious and avoidant attachment. The findings offer insights into both aggravating and protecting factors in couples’ responses to pandemic-related stressors.